"Artificial Intelligence + Health" Empowers New Quality Productivity - Yue XIAO; Zhiyang WANG (Yixue yu zhexue, 2025)
Currently, artificial intelligence (AI) technologies characterized by digitalization, intelligence, and greenness are developing rapidly in the health and wellness sector, driving the rise of new models, new business forms, and new industries such as precision medicine, proactive health, and the silver economy, which injects new impetus into the construction of a Healthy China. However, the medical and health sector still faces many challenges in the systematic application of AI technologies. For instance, the privacy protection and security of medical data need to be urgently addressed; the explainability and clinical applicability of AI technologies need to be further enhanced; and the lack of standardization and regulatory frameworks may lead to uneven application of the technology and potential risks. To address these challenges, it is necessary to strengthen scientific governance, improve digital infrastructure construction, promote multi-scenario integration, and ensure that technological innovation aligns with social needs, so as to achieve the high-quality development goals in the health and wellness sector.